STUDENTS’ PERSPECTIVE ON ROLE-PLAY AND PREVIEW /REVIEW TEACHING METHODS IN LEARNING VOCABULARY: A COMPARATIVE STUDY - ELLI MARLIANA; CHARIZKI MULYADI (GANEC SWARA, 2023)
This research delves into the challenges faced by students at STKIP Paracendekia NW Sumbawa in their pursuit of English language proficiency, with a specific focus on vocabulary acquisition, a fundamental aspect of language learning. Through a qualitative lens, this study delves into the effectiveness of two teaching methods: Role-Play and Preview/Review. The findings underscore the advantages of the Role-Play method in bolstering vocabulary comprehension, while simultaneously shedding light on the hurdles related to pronunciation and self-assurance. In a contrasting vein, the Preview/Review approach, leveraging students' native language and supplementary materials, emerges as a facilitator for efficient vocabulary acquisition. This research places a notable emphasis on the imperative need to address pronunciation challenges, boost students' self-confidence, and introduces a promising hybrid teaching strategy. The recommendations outlined encompass targeted interventions, the amalgamation of teaching methods, the promotion of effective learning strategies, and the dissemination of these findings as a valuable educational resource. In sum, this study significantly contributes to the realm of English language education at STKIP Paracendekia NW Sumbawa. It not only offers practical insights for educators and institutions but also strives to enhance the overall vocabulary learning experience for students, thereby adding a valuable dimension to the educational landscape.